- PENYAKIT HUNTINGTON : SEBUAH LAPORAN KASUS DAN ULASAN SINGKAT: - - Richard Suherlim (PERDOSNI, 2022)
Huntington's disease is an autosomal dominant hereditary disease that is very rare in Indonesia. This disease is characterized by involuntary movement disorders in the form of chorea that worsens from distal to proximal. Patients with Huntington's disease usually have impaired cognitive function and psychiatric disorders. The diagnosis was obtained from clinical examination, family history, and confirmed by genetic examination where a mutation in the HTT gene that encodes for the CAG trinucleotide repeats more than 35 times resulted in a toxic protein called huntingtin. Huntington's disease does not have a therapeutic regimen that can cure or slow its progression. Patients will only receive symptomatic therapy aimed at maintaining quality of life. Huntington's patients have a poor prognosis, with a median mortality of 17-20 years after symptom onset. This article reports a 76-year-old female patient, an Indonesian citizen, who had symptoms of chorea and impaired cognitive function with onset 10-15 years ago. The patient has a mother, sister, and children who also have similar symptoms. The patient was suspected of having Huntington's disease, but could not be confirmed because no genetic examination was performed. The patient did not receive any form of therapy for his illness.